Ulasan Singkat Profil Fitokimia dan Aktivitas Biologi dari Daun Kratom - Dikianur Alvianto; Panggulu A R Utoro; Jatmiko E Witoyo; Adhian D Khoirina; Nelsy D Permatasari; Lisa F Rahayu (Universitas Pattimura, 2025)
Mitragyna speciosa leaves are one of the most widely utilized parts of the kratom plant by local communities in several ASEAN countries, including Indonesia, Malaysia, and Thailand, particularly for traditional medicine. However, comprehensive knowledge regarding the morphology, phytochemical profile, and bioactivity of M. speciosa leaves from Indonesia remains limited. Therefore, this study aims to comprehensively explore the morphology, phytochemical profile, and bioactivity of M. speciosa leaves from Indonesia. This study employs a literature review method, using data sourced from scientific journal articles, conference proceedings, and various online publications available through open-access platforms from 2015 to 2025. The results indicate that the morphology of M. speciosa leaves in Indonesia can be categorized into three types: white, red, and green. Qualitative phytochemical tests have revealed the presence of bioactive compounds with specific functions, including alkaloids, flavonoids, saponins, tannins, phenolics, quinones, and mitragynine. Several recent studies have demonstrated that M. speciosa leaf extracts exhibit various bioactivities, including antibacterial, anti-inflammatory, antidiabetic, antioxidant, and anticancer effects. Future research is expected to optimize the extraction process of these bioactive compounds with greater efficiency and cost-effectiveness, and to further explore their potential applications in both the food and non-food industries.